Lingual vascular canal assessment by dental computed tomography: A retrospective study - Prashant Jaju; Sushma Jaju (Wolters Kluwer Medknow Publications, 2011)
Background: Lingual vascular canal (LVC) is an important anatomical structure in mandibular anterior region. Trauma to this structure during implant placement has been reported in this study. Dental computed tomography (DCT) provides a three-dimensional visualization of lingual vascular canal. Aim: To assess the frequency, location, and size of LVC using dental CT. Materials and Methods: A retrospective analysis of 75 mandibular DCT was done. Evaluation was done to detect the frequency, size, and number of lingual vascular canal using Seimens Somatom Sensation 64. Results: About 73.3% patients (male=34, female=21) demonstrated presence of LVC with only one patient showing two canals. The mean distance from the inferior border of mandible was 0.5 mm, S.D.±0.70. The mean diameter of the canal was 0.31 mm, S.D.±0.70. Conclusion:Dental CT provides adequate information regarding frequency, number, and size of lingual vascular canal, which is an important anatomical structure in mandibular anterior region.